2022
DOI: 10.1007/s00423-022-02443-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative fluid balance and outcomes after Pancreaticoduodenectomy: a retrospective study in 301 patients

Abstract: Background The incidence of postoperative morbidity after pancreaticoduodenectomy (PD) is high; however, whether fluid management after surgery affects postoperative morbidity is unclear. This study aimed to determine whether fluid balance in patients undergoing PD is associated with postoperative complications and mortality. Methods Data from a computer-based database of patients who underwent PD between 2016 and 2019 were retrospectively analyzed. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some studies tend to support restrictive fluid management, but the controversy over fluid management has never ceased. Zhang et al enrolled 301 patients for a retrospective study, and the results showed that higher postoperative fluid balance appeared to be associated with morbidity after PD, systemic inflammatory response syndrome (SIRS), acute respiratory distress syndrome (ARDS), bleeding, and heart failure [17]. However, Meyhoff et al performed an international, randomized trial among adult patients with septic shock in the ICU and found that intravenous fluid restriction did not decrease mortality at 90 days compared with standard intravenous fluid therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies tend to support restrictive fluid management, but the controversy over fluid management has never ceased. Zhang et al enrolled 301 patients for a retrospective study, and the results showed that higher postoperative fluid balance appeared to be associated with morbidity after PD, systemic inflammatory response syndrome (SIRS), acute respiratory distress syndrome (ARDS), bleeding, and heart failure [17]. However, Meyhoff et al performed an international, randomized trial among adult patients with septic shock in the ICU and found that intravenous fluid restriction did not decrease mortality at 90 days compared with standard intravenous fluid therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies tend to support restrictive uid management, but the controversy over uid management has never ceased. Zhang et al enrolled 301 patients for a retrospective study, and the results showed that higher postoperative uid balance appeared to be associated with morbidity after PD, systemic in ammatory response syndrome (SIRS), acute respiratory distress syndrome (ARDS), bleeding, and heart failure (17). However, Meyhoff et al performed an international, randomized trial among adult patients with septic shock in the ICU and found that intravenous uid restriction did not decrease mortality at 90 days compared with standard intravenous uid therapy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that preoperative undernutrition is associated with postoperative complications and poor prognoses in patients with malignant diseases [3][4][5]. The geriatric nutritional risk index (GNRI), which is calculated from serum albumin level and body mass index (BMI), was rst reported by Bouilanne et al for assessing nutritional status in older patients [6].…”
Section: Introductionmentioning
confidence: 99%